Non-proliferation in areas of limited statehood: The contribution of international regimes to controlling mass destruction capacities in war and crisis zones - Oliver Meier (Stiftung Wissenschaft und Politik (SWP), 2017)
Controlling nuclear, biological or chemical weapons is often particularly difficult where the proliferation risks are high: in areas of limited statehood. This raises the question of how to adapt international regimes so that they are better able to contribute to the disarmament and non-proliferation of weapons of mass destruction (WMD) under the challenging conditions of war and crisis. Experiences over the past few years in states such as Iraq, Libya and Syria - where central governments do not completely control the respective state's territory - have been mixed. They do show, however, that multilateral non-proliferation regimes play an indispensable role in controlling WMD, including in crisis areas. First, it is important to gain and focus the political support of the state in question, the relevant great powers and international organisations. Second, the practical conditions for a mission to secure and disarm WMD and investigate alleged use of such weapons have to be established. To obtain these goals, existing rules should be made flexible and adapted. Regimes should be reformed in line with the motto, "As few rules as necessary, as much preparation as possible". Four aspects need to be kept in mind: prevention should be reinforced, crisis planning needs to be improved, stakeholders have to be included, and the role of the Security Council should be upgraded. Medium-size powers such as Germany have the capacities and political weight to promote the evolution of global regulatory instruments. This would also counteract proliferation in Europe's neighbourhood.
Keywords: 320